Indonesian mining companies' social responsibility performance: the role of ownership structure and sharia compliance - Muhamad Umar Mai; Mochamad Edman Syarief; Iwan Setiawan; Dian Imanina Burhany; Nafisah Ruhana; Hanudin Amin; Mohd Raziff Jamaluddin (Cogent Business & Management, 2024)
Implementing and communicating Corporate Social Responsibility (CSR) is the primary foundation for businesses to accomplish the Sustainable Development Goals. In this perspective, mining operations are seen as one of the most harmful corporate activities when compared to other businesses that utilize natural resources; therefore, these companies must strongly implement and demonstrate higher CSR. The Feasible Generalized Least Squares (FGLS) model was employed in this study to investigate the role of ownership structure and Sharia compliance in improving the CSR performance of Indonesian mining companies that were operated between 2012 and 2021. The findings reveal that institutional ownership, foreign ownership, and Sharia compliance are essential factors in increasing mining companies' CSR performance, but state ownership and ownership concentration are not. This study addresses a vacuum in the current CSR literature for mining businesses. Furthermore, it gives extra information and insight for practitioners, including the Indonesian government as the CSR regulator, investors, management, and non-governmental organizations (NGOs). This is one of the first studies to examine ownership structure and Sharia compliance in relation to mining companies' CSR performance, notably in Indonesia, Feasible Generalized Least Squares.
Keywords: 650; CSR performance; Indonesian mining companies; ownership structure; sharia compliance; feasible generalized least squares